Cohesion policy in the outermost regions (European Union, 2024)
This study focuses on EU Cohesion Policy in the nine outermost regions. It first outlines the geographic, climate, socio-economic, demographic and administrative characteristics of these regions and further analyses the vulnerabilities affecting their convergence processes. It pays particular attention to the implementation of EU Cohesion Policy and the use of place-based approaches to foster their economic growth. Finally, it reviews the importance of Article 349 of the TFEU and concludes with recommendations for its wider application.
10.2861/000408
Keywords: Graue Literatur; Amtliche Publikation; EU-Regionalpolitik; EU-Strukturfonds; Wirtschaftliche Konvergenz; Überseegebiete; EU-Staaten; adaptation to climate change; economic and social cohesion; EU regional policy; regional cooperation; economic growth; sustainable development; environmental protection; report